Decomposing Financial Risks and Vulnerabilities in Eastern Europe - Worrell, Rupert (IMF Working Papers; Working Paper ;, 2007)
This paper assesses how various types of financial risk such as credit risk, market risk, and liquidity risk affect banking stability in the ten countries that joined the European Union most recently, and eight neighboring countries. It also examines how the quality of supervisory standards may have mitigated the vulnerabilities arising from these risk factors. Using panel data, the study finds substantial variation in the impacts of financial risks, the macroeconomic environment, and supervisory standards on banks' risk profile across different country clusters. Credit quality is of general concern especially in circumstances where credit growth is accelerating.